NORMATIVE LAW REVIEW: PMIK WORKLOAD CHALLENGES IN FACING THE RME ERA - Ninda, Rahmaninda Putri Gading; Lilik Afifah; Achmad Jaelani Rusdi (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2024)
In carrying out the process of processing health data and information, Medical Recorder and Health Information (PMIK) personnel are needed who have the ability to provide services to patients. The emergence of the Minister of Health Regulation Number 24 of 2022 concerning electronic medical records requires every health care facility to run electronic medical records, this makes the workload owned by PMIK reduced. So it is necessary to analyze the challenges of PMIK workload in facing the RME era. The method used is qualitative with a normative law study approach. The approach used for data collection is based on documentation studies through regulations, journals, and news. The tool used for data collection is a notebook. Data processing techniques using secondary data. In carrying out their duties, many Medical Recorders and Health Information (PMIK) still do not understand the use of existing systems properly, this causes delays in the processing of medical data. The abilities possessed by PMIK personnel in the RME era greatly affect the patient data processing process so that it is necessary to conduct training and skill development related to the correct use of the RME system in order to reduce the workload faced by officers.